2012
DOI: 10.1111/ctr.12001
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion of organ donation: a survey in Iran

Abstract: There should be simple processes for the public to declare their decision about organ donation in case of brain death. People should be encouraged to communicate their wishes with others so that family members can decide about their organ donation more easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…In a cross-sectional survey of 125 family members of potential organ donors under brain death criteria conducted in Southern Iran between 2009 and 2010, a majority (58.4%) of families refused organ donation, 30.1% of which did so based on a belief in the possibility of a miracle and the recovery of the patient 19. Similar beliefs about recovery were reported in a study conducted in India,39 a qualitative study in Sweden,53 a study of university students47 and a study of the Iranian public 44…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In a cross-sectional survey of 125 family members of potential organ donors under brain death criteria conducted in Southern Iran between 2009 and 2010, a majority (58.4%) of families refused organ donation, 30.1% of which did so based on a belief in the possibility of a miracle and the recovery of the patient 19. Similar beliefs about recovery were reported in a study conducted in India,39 a qualitative study in Sweden,53 a study of university students47 and a study of the Iranian public 44…”
Section: Resultsmentioning
confidence: 65%
“…Two additional articles assessing knowledge of brain death's legal connection to death similarly reported that a minority of the study population was able to identify brain death as the legal equivalent of death 48 49. In one Iranian study, 61.2% did not know if laws existed on organ donation in Iran; 21.1% incorrectly believed there were no laws regulating organ donation 44. One study published in 1985 (and possibly conducted before the Uniform Definition of Death Act) found that 55.1% of individuals thought brain death should be the legal definition of death 50.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of valid scientific and theological objections, many Sunni and Shiite scholars continue to espouse the permissibility of end-of-life organ donation [71,72]. One implication of reinterpreting religious text for the benefit of a utilitarian transplantation practice is that religion’s primary value, ie, the sanctity of life and human dignity is being violated.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent survey of religious officials, Tarhan et al reported 92% had favorable views to organ donation [74]. Nondisclosure of the medical, legal, and religious controversies about the death criteria and organ donation was a common theme in public surveys [27-29,71,72,74,75]. Surveyors did not discern willingness to organ donation if the death criteria were inconsistent with the Islamic moral code.…”
Section: Introductionmentioning
confidence: 99%
“…It is also data collected after the new national regulations governing compensated organ donation were fully implemented and includes donor interviews done in six transplant regions instead of just at one hospital in Shiraz. Iranians have written papers based on interviews with living organ donors, but none focused on the question of exploitation other than Zargooshi, and his data were collected even before Tober's (1989–2000) (Broumand, Parsapoor, & Asghari, ; Farahani & Esmaeili, ; Zargooshi, , ). Furthermore, none of the raw data (recordings or field notes) are publically available for any of these authors.…”
Section: Introductionmentioning
confidence: 99%